2022
DOI: 10.1097/md.0000000000029413
|View full text |Cite
|
Sign up to set email alerts
|

Alternating hemiplegia of childhood: a distinct clinical entity and ATP1A3-related disorders: A narrative review

Abstract: Alternating Hemiplegia of Childhood (AHC) is a rare disorder with onset in the first 18 months of life characterized by stereotyped paroxysmal manifestations of tonic and dystonic attacks, nystagmus with other oculomotor abnormalities, respiratory and autonomic dysfunctions. AHC is often associated with epileptic seizures and developmental delay. Hemiplegic paroxysm is the most remarkable symptom, although AHC includes a large series of clinical manifestations that interfere with the disease course. No cure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
(194 reference statements)
0
3
0
Order By: Relevance
“…Pavone et al revealed that patients with persistent neurological findings compared to paroxysmal episodes, in which migraine, fine and gross motor dysfunction, walking disturbances, speech problems, and cognitive impairments are found, will more commonly have these features throughout their lives. 86 …”
Section: Prognosismentioning
confidence: 99%
“…Pavone et al revealed that patients with persistent neurological findings compared to paroxysmal episodes, in which migraine, fine and gross motor dysfunction, walking disturbances, speech problems, and cognitive impairments are found, will more commonly have these features throughout their lives. 86 …”
Section: Prognosismentioning
confidence: 99%
“…[2][3][4][5][6] For example, various mutations found in the ATP1a3 gene have been identified in several cases of COS, indicating that this gene potentially influences the development of the illness. 7 In addition to the phenotypic and genetic differences between COS and adult-onset schizophrenia, COS inherently disrupts developmental trajectories at an earlier age and at different stages of development. This disruption may go unnoticed or untreated for a longer period than adult-onset schizophrenia, with the average time to treatment estimated at around 3.5 times longer for COS than for adult-onset schizophrenia.…”
Section: Questions To the Consultantsmentioning
confidence: 99%
“…Additionally, there seems to be a stronger correlation between genetic markers, such as single nucleotide polymorphisms and copy number variants, thought to be risk factors for schizophrenia 2-6 . For example, various mutations found in the ATP1a3 gene have been identified in several cases of COS, indicating that this gene potentially influences the development of the illness 7 …”
Section: Questions To the Consultantsmentioning
confidence: 99%